2013
DOI: 10.1242/dev.093716
|View full text |Cite
|
Sign up to set email alerts
|

ERF and ETV3L are retinoic acid-inducible repressors required for primary neurogenesis

Abstract: SUMMARYCells in the developing neural tissue demonstrate an exquisite balance between proliferation and differentiation. Retinoic acid (RA) is required for neuronal differentiation by promoting expression of proneural and neurogenic genes. We show that RA acts early in the neurogenic pathway by inhibiting expression of neural progenitor markers Geminin and Foxd4l1, thereby promoting differentiation. Our screen for RA target genes in early Xenopus development identified Ets2 Repressor Factor (Erf) and the close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 98 publications
(131 reference statements)
1
26
0
1
Order By: Relevance
“…1D) (Chen, et al , 2013), the latter of which forms a winged helix-turn-helix (wHTH) motif that binds DNA elements approximately 10 basepairs long that contain the motif GGAA/T (Dittmer and Nordheim, 1998). Additionally, etv5a belongs to the conserved ETS transcription factor family, which has been shown to have roles in tissue patterning as well as in ciliogenesis (Wasylyk, et al, 1998; Kobberup, et al , 2007; Mao, et al , 2009; Znosko, et al , 2010; Chen, et al , 2013; Janesick, et al , 2013). These previously described functional roles of etv5a in tissue development, together with the early onset of etv5a expression before mature MCCs can be detected and the continued expression of etv5a throughout the MCC domain at later time points, led us to hypothesize that etv5a was involved in MCC formation in the renal progenitor field.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1D) (Chen, et al , 2013), the latter of which forms a winged helix-turn-helix (wHTH) motif that binds DNA elements approximately 10 basepairs long that contain the motif GGAA/T (Dittmer and Nordheim, 1998). Additionally, etv5a belongs to the conserved ETS transcription factor family, which has been shown to have roles in tissue patterning as well as in ciliogenesis (Wasylyk, et al, 1998; Kobberup, et al , 2007; Mao, et al , 2009; Znosko, et al , 2010; Chen, et al , 2013; Janesick, et al , 2013). These previously described functional roles of etv5a in tissue development, together with the early onset of etv5a expression before mature MCCs can be detected and the continued expression of etv5a throughout the MCC domain at later time points, led us to hypothesize that etv5a was involved in MCC formation in the renal progenitor field.…”
Section: Resultsmentioning
confidence: 99%
“…There is also rich evidence that etv5a and its family members are downstream of FGF signaling in a myriad of tissues (Raible and Brand, 2001; Roehl and Nüsslein-Volhard, 2001; Mao, et al, 2009; Znosko, et al , 2010; Little and McMahon, 2012; Janesick, et al , 2013). In particular, research has demonstrated that etv5b and etv4 expression is completely lost after treatment with a pan-FGF inhibitor SU5402 (Roehl and Nüsslein-Volhard, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RARα or RARγ knockdown in the frog, Xenopus laevis, produces specific defects in neuronal differentiation, pre-placodal ectoderm formation and axial elongation (Janesick et al, 2014(Janesick et al, , 2013(Janesick et al, , 2012Koide et al, 2001). We have shown that RARγ is required for axial elongation and for maintenance of the caudal progenitor pool (Janesick et al, 2014).…”
Section: Introductionmentioning
confidence: 86%
“…The signature chevron somite shape is found in all aquatic creatures, and is indispensable for locomotion (Rost et al, 2014). RAR loss-of-function-induced paralysis in Xenopus was previously attributed to loss of primary neurons (Janesick et al, 2013;Sharpe and Goldstone, 1997;Blumberg et al, 1997). However, other factors that control locomotion (e.g.…”
Section: Rarβ2 Loss Of Function Reduces Somite Number and Increases Smentioning
confidence: 99%